Analisis Peran DPR dalam Menyuarakan Kepentingan Rakyat Berdasarkan Sila Keempat Pancasila - Nofita Rudiani Asbanu; Claudina Margarida Freitas Belo; Yakobus Adi Saingo (PT. PENERBIT TIGA MUTIARA, 2025)
The Constitution of the Unitary State of the Republic of Indonesia (NKRI) stipulates that the interests of the people must be voiced and accommodated through legislative channels, represented by the People's Representative Council (DPR) from the regional to the central government levels. However, it is often found that the hopes of the people are not fully articulated, resulting in certain issues never reaching a final resolution. This study aims to analyze the role of the DPR in voicing the people's interests based on the fourth principle of Pancasila. The method used in this research is qualitative with a literature study approach, where data is collected from various scientific sources. The results of the analysis show that the main functions of the DPR, namely in legislation, oversight, and budgeting, have not been fully optimized due to weak accountability and transparency. This crisis of representation impacts the decline in public trust, low political participation, and increased polarization in society. To address these issues, systemic reforms are needed, including enhancing transparency, strengthening accountability mechanisms, and involving the public actively in the decision-making process. Thus, the goal of the DPR’s existence, which can be achieved, is to voice the will of the people, realize deliberation for consensus, and ensure justice and welfare in line with the substance of Pancasila’s ideology, particularly its fourth principle. This study recommends the need to restore the essence of deliberation for consensus in accordance with the fourth principle of Pancasila, accompanied by better political education and electoral system reforms to ensure that elected representatives are truly competent and focused on the interests of the people.